Atuação e conquistas das mulheres na Assembleia Nacional Constituinte de 1988 - Broch, Marina (2021)
This dissertation focuses on women's participation in the 1988 National Constituent Assembly and aims to analyze how Brazilian women mobilized and the articulation of the members of the Lipstick Lobby in the National Constituent Congress. The concept of gender is used as a category of analysis and the concept of male domination in the social construction of the roles played by the sexes to contextualize the late occupation of women in positions of power. In this sense, the trajectory of women in Brazilian politics is highlighted, demonstrating how late the implementation of women's rights in the country's legal diplomas occurred, as a consequence of women's exclusion from these political environments. Thus, the importance of women's participation in the 1988 Constituent Assembly is observed, especially with regard to the role of the Lipstick Lobby. Through the approach regarding female organization in movements, associations and entities in defense of women's rights during the period of redemocratization, the Letter of Brazilian Women to the Constituents is used, which unified the demands of women in Brazil, and through the verification of the provisions contained in the Federal Constitution of 1988, which are achievements resulting from female participation in the National Constituent Assembly, it is evident that female articulation occurred in an organized, cohesive manner and was successful in most of the proposals, mainly with regard to women's rights.